TEACHERS’ MEANING NEGOTIATION STRATEGIES IN CONSTRUCTING SPEAKING SKILL THROUGH GOOGLE MEET - Siska Bellya Putri; Andi Rustandi; Didih Faridah (Journal of English Education Program (JEEP), 2022)
This research discusses teachers’ meaning negotiation strategies in constructing speaking skills through Google Meet. Meaning negotiation can show how well the teacher interacts with students. This study was aimed at finding out how the teacher negotiate meaning in constructing speaking skills and the students’ perceptions when the teacher used to mean negotiation strategies. The present study used a qualitative Case study design. Twenty students from 1A in Speaking for information Function and an English lecturer have participated in this study. The data were obtained through observation to research how do teachers’ meaning negotiate in constructing speaking skills in speaking class through Google Meet, interviews to collect data what the students’ perceptions towards meaning negotiation used by the teacher in speaking class. The observation data were analyzed based on 4 components from Pica (1991) namely trigger, signals, response, and follow-up. To analyze the interview data, the researcher first transcribes the data and then interprets it. The findings show that the 4 components of meaning negotiation used by the teacher were well-implemented. It also indicates that the teacher can provide more explanation. Furthermore, a teacher can help the students in understanding a new word and its meaning and making the conversation in the speaking class run well. This research concludes that meaning negotiation used by the teacher is a good tool and effective in the real situation. The teacher encourages them to practice solving communication problems occurring among them through meaningful negotiation. The researcher suggests that the teacher is expected to be more well organized in delivering material to construct a better conversation in their speaking skill.